Program P fails when either P1 fails or P2 fails, i.e. failure of P1 + failure of P2.
But this will also contain the case when both P1 and P2 fails at the same time, i.e. failure of P1 ∩ failure of P2, since this case will be already be counted on (P1+P2).
Therefore, our final answer will be failure of P1 + failure of P2 - (failure of P1 ∩ failure of P2)
= $\left ( \frac{50}{100} \right )$ + $\left ( \frac{40}{100} \right )$ -$\left ( \frac{50}{100} * \frac{40}{100}\right )$
= $\left ( \frac{90}{100} \right )$ - $\left ( \frac{2000}{10000} \right )$
= $\left ( \frac{90}{100} \right )$ - $\left ( \frac{20}{100} \right )$
= $\left ( \frac{70}{100} \right )$
= 70%